Use of pineapple waste for production of decomposable pots - I. Jirapornvaree; T. Suppadit; A. Popan (International Journal of Recycling of Organic Waste in Agriculture, 2017)
Abstract Purpose The aim of this research was to evaluate the suitability of pineapple waste for production of decomposable nursery pots. Methods The experiment was completely randomized, with three replicates and eighteen formula treatments. Treatments consisted of varying ratios of pineapple waste to binder, including 2:1, 1:0 (fresh pineapple waste), 1:1, 1:1.5, and 1:2; the textures tested were coarse, medium, and fine, and the pot thicknesses were 0.5, 1.0 and 1.5 cm. Results The results revealed that the physical and chemical properties of pineapple waste were suitable for use in nursery pots on an experimental scale. The optimal physical and chemical properties for a decomposable pot included a 1:0 ratio of pineapple waste to binder, a coarse structure, and a pot thickness of 1 cm. With these properties, the pot degraded in more than 45 days, N and P release rates were 0.49% and 7.97 mg-P/kg, respectively, and the average absorption rate was 258.43%. Saturation occurred in 45 min, and the water evaporated in 444 h. Conclusion In terms of cost production per pot, fresh pineapple waste cost 0.0075 USD for a three-and-a-half inch diameter decomposable pot (excluding logistical costs). Therefore, this study provides a possible method for waste management.